Peningkatan Kemampuan Analisis Struktur Teks Laporan Hasil Observasi (LHO) dengan Metode Colaborative Learning - Sajida Faidaah Al-afify; Kaswadi Kaswadi; Moch. Hadiyono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to improve the ability to analyze the text structure of the Report of Observation Results (LHO) in class X TITL 1 SMK Negeri 5 Surabaya through the application of collaborative learning methods. This research was conducted in two cycles. In cycle 1, most groups scored below the Minimum Completion Criteria (KKM). However, after improvements were made in cycle 2 by adding differentiation of the learning process according to students' learning modalities, there was a significant increase in scores. The results showed an increase in students' scores by 20% to 50%, with all groups successfully exceeding the KKM. Group 6 experienced the highest increase, from 50 to 100. This finding shows that the collaborative learning method is effective in improving the ability to analyze the structure of LHO text. The application of this method achieved maximum results, so it can be recommended as a learning strategy for similar materials in the future.